BIO-PORTA TANK (BACTERIAL PORTABLE SEPTICTANK) SEBAGAI SOLUSI SANITASI PERUMAHANDENGANMUKA AIR TANAH TINGGI [BIO-PORTA TANK (BACTERIAL PORTABLE SEPTICTANK) AS A SANITATION SOLUTION OF HOUSING WITH HIGH GROUNDWATER LEVEL] - Dhea Fitra Yofani; Shakila Fuadah Lubis; Milka Novita Manalu; Ramadhan Yanuari; Rezha Yaren; Gunawan Wibisono; Monita Olivia (Universitas Pelita Harapan, 2020)
Kubang Jaya village is located in a low land peat swampy area and often suffers from the flood in the rainy season. Swampy peat area generally has a high groundwater level; thus, it can immerse the septic tank in the housing in the area. The height of the groundwater table is approximately 50cm from the surface level, while the depth of the septic tank is 150cm. When the septic tank below groundwater level, this could cause a mix of soil water and septic tank waste. This community development activity aims to educate the community about sanitation and give lecture and training of installing bio-porta septic tank (bacterial portable septic tank) for housing in high groundwater level area. Bio-porta septic tank consists of two drums as sediment tank and aeration tank. Bio balls were used to speed up the decomposition by aerobic bacteria in the tank. An aerator was added to the installation to increase the proliferation of bacteria. The community development activities were pre-test, lecture, post-test, practical and cadre training. Results show that there was an increase of understanding and knowledge of community from 24% to 62% about the septic tank in high groundwater level area. The community also agreed to replace the conventional septic tank into the bio-porta septic tank in the future. The activity also has a positive impact on educating and changing the mindset and attitude the community of Kubang Jaya village in improving the sanitation with an intention to the bio-porta septic tank in the future.BAHASA INDONESIA ABSTRACT: Desa Kubang Jaya merupakan kawasan dataran rendah rawa gambut dan sering mengalami banjir saat musim hujan. Lahan rawa gambut umumnya memiliki muka air tanah tinggi sehingga dapat merendam tangki septik pada perumahan yang terdapat di kawasan tesebut. Rata-rata tinggi muka air tanah sekitar ±50 cm, sedangkan kedalaman tangki septik warga sekitar ±150 cm dari permukaan tanah. Apabila tangki septik terendam, maka hal ini dapat mengakibatkan pencampuran air tanah dengan limbah tangki septik. Oleh karena itu dilakukan kegiatan pengabdian masyarakat dengan memberikan pengetahuan mengenai sanitasi lingkungan dan memberikan penyuluhan serta pelatihan pembuatan tangki septik bio-porta (bacterial portable septic tank) untuk rumah di lingkungan dengan muka air tanah tinggi. Tangki septik bio-porta terdiri dari dua drum yang berfungsi sebagai tangki pengendapan dan tangki aerasi. Untuk mempercepat proses penguraian oleh bakteri aerob di dalam tangki maka digunakan bio ball atau rumah bakteri. Aerator ditambahkan pada instalasi untuk mempercepat perkembangbiakan bakteri aerob. Kegiatan pengabdian terdiri dari pre-test, penyuluhan, post-test, praktek, dan pelatihan kader. Hasil evaluasi kegiatan pengabdian menunjukkan terjadinya peningkatan pengetahuan masyarakat dari 24% menjadi 62% tentang tangki septik di lahan dengan muka air tanah tinggi. Masyarakat juga sangat setuju untuk mengganti tangki septik konvensional dengan tangki septik bio-porta di masa mendatang. Hasil kegiatan sangat berdampak positif untuk mengedukasi dan mengubah pola pikir serta sikap warga desa Kubang Jaya dalam memperbaiki sanitasi lingkungan tempat tinggal dengan keinginan untuk menggunakan tangki septik bio-porta di masa mendatang.